2x(x+4)(6)=16

Simple and best practice solution for 2x(x+4)(6)=16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x(x+4)(6)=16 equation:


Simplifying
2x(x + 4)(6) = 16

Reorder the terms:
2x(4 + x)(6) = 16

Reorder the terms for easier multiplication:
2 * 6x(4 + x) = 16

Multiply 2 * 6
12x(4 + x) = 16
(4 * 12x + x * 12x) = 16
(48x + 12x2) = 16

Solving
48x + 12x2 = 16

Solving for variable 'x'.

Reorder the terms:
-16 + 48x + 12x2 = 16 + -16

Combine like terms: 16 + -16 = 0
-16 + 48x + 12x2 = 0

Factor out the Greatest Common Factor (GCF), '4'.
4(-4 + 12x + 3x2) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(-4 + 12x + 3x2)' equal to zero and attempt to solve: Simplifying -4 + 12x + 3x2 = 0 Solving -4 + 12x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. -1.333333333 + 4x + x2 = 0 Move the constant term to the right: Add '1.333333333' to each side of the equation. -1.333333333 + 4x + 1.333333333 + x2 = 0 + 1.333333333 Reorder the terms: -1.333333333 + 1.333333333 + 4x + x2 = 0 + 1.333333333 Combine like terms: -1.333333333 + 1.333333333 = 0.000000000 0.000000000 + 4x + x2 = 0 + 1.333333333 4x + x2 = 0 + 1.333333333 Combine like terms: 0 + 1.333333333 = 1.333333333 4x + x2 = 1.333333333 The x term is 4x. Take half its coefficient (2). Square it (4) and add it to both sides. Add '4' to each side of the equation. 4x + 4 + x2 = 1.333333333 + 4 Reorder the terms: 4 + 4x + x2 = 1.333333333 + 4 Combine like terms: 1.333333333 + 4 = 5.333333333 4 + 4x + x2 = 5.333333333 Factor a perfect square on the left side: (x + 2)(x + 2) = 5.333333333 Calculate the square root of the right side: 2.309401077 Break this problem into two subproblems by setting (x + 2) equal to 2.309401077 and -2.309401077.

Subproblem 1

x + 2 = 2.309401077 Simplifying x + 2 = 2.309401077 Reorder the terms: 2 + x = 2.309401077 Solving 2 + x = 2.309401077 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 2.309401077 + -2 Combine like terms: 2 + -2 = 0 0 + x = 2.309401077 + -2 x = 2.309401077 + -2 Combine like terms: 2.309401077 + -2 = 0.309401077 x = 0.309401077 Simplifying x = 0.309401077

Subproblem 2

x + 2 = -2.309401077 Simplifying x + 2 = -2.309401077 Reorder the terms: 2 + x = -2.309401077 Solving 2 + x = -2.309401077 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = -2.309401077 + -2 Combine like terms: 2 + -2 = 0 0 + x = -2.309401077 + -2 x = -2.309401077 + -2 Combine like terms: -2.309401077 + -2 = -4.309401077 x = -4.309401077 Simplifying x = -4.309401077

Solution

The solution to the problem is based on the solutions from the subproblems. x = {0.309401077, -4.309401077}

Solution

x = {0.309401077, -4.309401077}

See similar equations:

| 2w-5w=12 | | -5(3p+4)-10=4(4p+8) | | 8=y-10 | | -86+5y+6=5(3y-3)-5 | | 7(6x-8)=70 | | 5x^3+20x^2+20= | | 5(c-3)=6(c-6) | | 21x^2-5x-4=0 | | 4(3x+5)=44 | | 18=6x-12 | | y^4-y=0 | | 6x^4-24x^2=0 | | 3x^2+3x-7=0 | | m^2=-4 | | 18(5c-1)-16=88c+18 | | 104-92=32y-35y | | -15s-34+5(3s+8)=0 | | x-56=53 | | 12m-3m^2=9 | | 5m-11m=18 | | 8-8=19t-18t | | 3r-13r=20 | | 2(x+3)-4x=3x-2(2x-1) | | 10x+8=8x+9 | | -2+12=4b-8-3b | | 7x^2+5x-2=0 | | 12=x+4 | | 9u-56v+32= | | 13x=7x+30 | | 5+3(2n+5)-n= | | 12x-6=4x+26 | | 7+3(4n+2)-n= |

Equations solver categories